Music and the historical imagination - Treitler, Leo 1931- (Cambridge Harvard university press, 1989)
Leo Theitler is a central figure in American musicology, both for his writings on medieval and Renaissance music and for his influential work on historical analysis. In this elegant book he develops a powerful statement of what music analysis and criticism in relation to historical understanding can be. His aim is an understanding of the music of the past not only in its own historical context but also as we apprehend it now, and as we assimilate it to our current interests and concerns. He elucidates his views through unique new interpretations of major works from the fifteenth through the twentieth centuries.